2022
DOI: 10.1186/s12967-022-03695-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of probiotic administration on patients with prediabetes: a meta-analysis and systematic review

Abstract: Background This paper aimed to examine the effects of probiotics on eight factors in the prediabetic population by meta-analysis, namely, fasting blood glucose (FBG), glycated haemoglobin A1c (HbA1c), homeostatic model assessment of insulin resistance (HOMA-IR), quantitative insulin sensitivity check index (QUICKI), total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C), and the mechanisms of action are summarized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 89 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…Our research has recommended that probiotics could improve HOMA-IR and HDL in managing glucose homeostasis. However, previous studies [ 28 ] have shown that probiotics do not have a statistically significant effect on HOMA-IR and HDL. The main reason is the differences in the included articles.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our research has recommended that probiotics could improve HOMA-IR and HDL in managing glucose homeostasis. However, previous studies [ 28 ] have shown that probiotics do not have a statistically significant effect on HOMA-IR and HDL. The main reason is the differences in the included articles.…”
Section: Discussionmentioning
confidence: 92%
“…Compared to a recent study [ 28 ], there are some novelties in our work. Firstly, considering the differences between adolescents and adults, we only explored the effects of probiotics on prediabetes in adults.…”
Section: Discussionmentioning
confidence: 95%
“…Oh et al 30 reported a significant decrease in HbA1c in 40 participants with prediabetes taking L. plantarum HAC01 for 8 weeks; however, studies involving an intake of ≥12 weeks provide valuable information. A recent meta‐analysis and systematic review showed that probiotics could decrease HbA1c levels in patients with prediabetes; none of the adopted studies was sufficient to evaluate the post‐observation period after discontinuation 31 . The 8‐week post‐observation period in the current study considered the time‐related characteristics of changes in HbA1c levels and allowed us to assess properly the impact of food interventions on these levels.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis and systematic review showed that probiotics could decrease HbA1c levels in patients with prediabetes; none of the adopted studies was sufficient to evaluate the post-observation period after discontinuation. 31 The 8-week post-observation period in the current study considered the time-related characteristics of changes in HbA1c levels and allowed us to assess properly the impact of food interventions on these levels.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis, therefore, concluded that probiotics may play an important role in the regulation of HbA1c, QUICKI, total and LDL cholesterol, and TG in patients with prediabetes. Furthermore, based on existing studies, probiotics can regulate blood glucose homeostasis in various ways [154].…”
Section: Dietary Supplementation With Probioticsmentioning
confidence: 99%